The Inhibitory Effect of the Active Ingredients in the Bushen Huoxue Formula on the IL-17A Signaling Pathway and Its Alleviating Effect on Osteoarthritis - Wang X; Zhang Y; Chang X; Wen X; Tian F; Yu H; Li Y (Journal of Inflammation Research)
Xuan Wang,1,* Yunheng Zhang,1,* Xin Chang,1 Xiaodong Wen,1 Feng Tian,1 Hanjie Yu,2 Yi Li1 1Department of Foot and Ankle Surgery, Honghui Hospital, Xi’an Jiaotong University, Xi’an, People’s Republic of China; 2Laboratory for Functional Glycomics, College of Life Sciences, Northwest University, Xi’an, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yi Li, Email footankle08@126.comObjective: Osteoarthritis (OA) stands as a prevalent degenerative disease worldwide. Despite the demonstrated therapeutic efficacy of the Bushen Huoxue formula (BSHXF) in treating OA, its underlying mechanism remains elusive. Network pharmacology is commonly employed for investigating drug–disease associations and processes. In this study, we employed network pharmacology alongside in vitro and in vivo experiments to elucidate the molecular mechanism by which BSHXF treats OA.Methods: Based on the TCMSP database, active components of BSHXF were screened, and OA-related targets were retrieved from GeneCard and DisGeNET to construct a “component-target-pathway” network using Cytoscape. Core target functions and pathways (KEGG/GO) were analyzed through STRING and Metascape, while component-target binding affinity was validated via Autodock. For in vitro experiments, an IL-1β-induced chondrocyte inflammation model was established, and key protein expression was detected by Western blot and immunofluorescence. For in vivo experiments, an OA model was created by medial meniscectomy of the knee joint in rats, and therapeutic efficacy was assessed using histological staining and micro-CT.Results: This study screened 89 active ingredients of BSHXF and identified 189 common targets. Network pharmacological analysis revealed luteolin and tanshinone IIA as the most crucial active ingredients in treating OA with BSHXF. The potential mechanisms of action for BSHXF in OA treatment involve inflammation inhibition, immune function regulation, and resistance to oxidative stress, with a significant regulatory role played by the IL-17 signaling pathway. Molecular docking results demonstrated luteolin’s strong binding affinity to key targets such as B-cell lymphoma 2 (Bcl-2), Matrix metalloproteinase-9 (Mmp-9), and IL-6.In vitro experiments demonstrated that BSHXF significantly suppressed IL-1β-induced inflammatory responses in chondrocytes, downregulating IL-17A expression (p < 0.05), reducing the expression of MMP-9 (p < 0.05) and IL-6 (p < 0.05), and inhibiting apoptosis. Additionally, in vivo experiments revealed that the high-dose BSHXF group (150 mg/kg) markedly alleviated cartilage damage in OA rats, with OARSI scores significantly decreased compared to the model group (p < 0.05). Micro-CT analysis showed that BSHXF inhibited osteophyte formation and ameliorated OA pathological conditions.Conclusion: BSHXF has the potential to alleviate OA by suppressing inflammation, inhibiting cartilage apoptosis and hindering extracellular matrix degradation via the IL-17 signaling pathway. Our study elucidated the molecular mechanisms underlying the therapeutic effects of BSHXF on OA, thus highlighting its further research implications as a novel drug candidate.Keywords: osteoarthritis, Bushen Huoxue formula, pharmacological mechanism, network pharmacology, experimental verification